Commentary on Jecker - Sorell, Tom (2021)
Jecker’s paper focuses on the value of sex and sexuality in the lives of older people, and she argues that there is nothing wrong with the use of sex robots to realise that value. She concedes that sex robots marketed today are overwhelmingly designed for heterosexual males, and that their appearance corresponds to certain objectionable stereotypes of sexually attractive women, and of exciting sexual practices. Still, she says, sex robots do not have to be like that, and a less stereotype-ridden design could take away the sexism, heterosexualism and ageism of current ones. I am sympathetic to these conclusions. But I believe that they are not general enough, and I want to take issue with the argumentative strategy that leads to them.The conclusions are not general enough, because disability or bad circumstantial luck can lead to the damaging absence of sex in the lives of people from many adult age groups, not just people in their 70s and 80s. Jecker’s paper starts with the case of couples whose sex life deteriorates with old age. But there are also many people, whether disabled or not, who fail to acquire a sex life, and who want one, sometimes desperately. They, too, have a problem that a suitable sex robot might help …